Optimal Treatment of Water using Linear Programming A case Study of Sunyani Water Treatment Plant - Koufie, Moses (2016)
A thesis submitted to the Department of Mathematics, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of Master of Science in Industrial Mathematics, Institute of Distance Learning. June 2011.